Dynamics of the gut microbiome of Asian seabass (Lates calcarifer) following oral vaccination and challenge with virulent Vibrio harveyi - Sutra, Jumria; Mohd Hashim, Amalia; Yusof, Mohd Termizi; Al-Saari, Nurhidayu; Nasruddin, Nurrul Shaqinah; Saad, Mohd Zamri; Zahaludin, Amir-Danial; Md Yasin, Ina Salwany; Azmai, Mohammad Noor Amal (Elsevier, 2025)
This study investigates the dynamics of the gut microbiome of Asian seabass following oral vaccination and challenge with virulent Vibrio harveyi. Fish were divided into vaccinated and non-vaccinated groups and fed either with commercial pellets containing an inactivated V. harveyi Vh1 vaccine or commercial pellets only. The feed-based vaccine was administered at weeks 0 (prime vaccination), 2 (first booster) and 6 (second booster) for the field testing, and the fish were transferred and challenged with 108 CFU/mL of virulent V. harveyi Vh1 in the laboratory at 70 days after prime vaccination. Gastrointestinal samples were aseptically collected at pre-vaccination, post-vaccination, and post-challenge for 16S amplicon sequencing. The gut microbial diversity and richness of the vaccinated group were drastically increased following the vaccination regimen but sustained following the bacterial challenge. However, for the non-vaccinated group, the diversity and richness slightly increased as the fish grow throughout the culture period but drastically increased following the bacterial challenge. The post-challenge phase revealed that Firmicutes, Fusobacteria, Bacteroidetes, Photobacterium, and Cetobacterium were higher in the vaccinated fish, whereas Proteobacteria, Actinobacteria, Shewanella, Vibrio, and Clostridium were higher in non-vaccinated group. Potential KEGG ortholog biomarkers that involve in quorum sensing pathway were identified only in the non-vaccinated group at post-challenge. Post-challenge showed a significant difference of relative percentage survival between the vaccinated (80 %) and non-vaccinated (0 %) groups. This study showed that feed-based vaccination helps to sustain the gut microbiota stability and reduce the mortality following Vibrio infection.